THE INFLUENCE OF VILLAGE FUNDS ON COMMUNITY WELFARE IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS IN THE DISTRICTS OF BENGKULU PROVINCE - Syabina Ketrin Purwani; Azansyah Azansyah (SEAN Institute, 2023)
This study aims to analyze the effect of village funds and gross regional domestic product on the human development index through poverty mediation in Bengkulu Province in 2016-2022. The data used is secondary data. This research uses path analysis method. The results of this study indicate that village funds have a negative effect on poverty in achieving the first sustainable development goal, namely poverty alleviation. Village funds have a significant effect on the human development index, which means in achieving the tenth sustainable development goal of reducing inequality in Bengkulu Province in 2016-2022. . Poverty cannot mediate the effect of village funds on the Human Development Index, while poverty can mediate gross regional domestic product on the human development index. Poverty in this study only mediates the effect of village funds and gross regional domestic product on the human development index in Bengkulu Province in 2016-2022.